LEARNING PROFESSIONALISM: MEDICAL STUDENTS’ PERSPECTIVE ON IDENTIFYING CLINICAL STAFFS’ BEHAVIOUR - Fithriyah C. Ummah; Gandes Retno Rahayu; Yayi Suryo Prabandari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Role modeling is known as one of the most effective methods in learning professionalism, especially in the workplace. Each role model shows a different substantial values of professionalism, therefore the 'positive' or 'negative' role model criterion are difficult to set. This study aims to understand how students identify 'professional behavior’ (positive role model) and ‘unprofessional behavior’ (negative role model).Method: The design was a qualitative with case study approach. The sample was 20 students of undergraduate medical school at one university in Indonesia, selected by purposive sampling using maximum variation strategy. Gender, GPA, origin, and clinical rotation are used as key dimensions. Data collection used two methods, written narrative and focus group discussion. While the steps of qualitative analysis refers to Miles and Huberman.Results: This study found four themes as ‘behavioral identification’, namely: 'self-principle', 'self-standard of professionalism', 'normative standard of professionalism' and 'subjectivity'.Conclusion: Differences in identification are a reflection of students’ cognitive maturity. The outcome of learning professionalism can be improved from ‘valuing’ to ‘organizing’ and ‘internalizing’ through role model exposure and facilitation that provides the opportunity to explore and to reflect on professional values, before the student chooses them independently. This is part of the development of internal belief systems that are closely related on how students build their professional identity.